Comprehensive Analysis of the Transcriptome-wide m6A Methylome in Lung Adenocarcinoma by MeRIP Sequencing - Mao, Wenli; Yu, Qingzhen; Wang, Kefeng; Ma, Qiang; Zheng, Yuxin; Zhang, Guojun; Luo, Wei; Wang, Nianwu; Wang, Yukun (Frontiers in Oncology, 2022)
N6-methyladenosine (m6A) is the most abundant internal modification on eukaryotic mRNAs. There is increasing evidence that m6A plays a key role in tumor progression, so it is important to analyze m6A modifications within the transcriptome-wide in lung adenocarcinoma (LUAD). Three pairs of LUAD samples and tumor-adjacent normal tissues were obtained from the South University of Science and Technology Hospital. And then methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq) were used to identify differential m6A modifications between tumor and tumor-adjacent normal tissues. We identified 4041 aberrant m6A peaks, of which 1192 m6A peaks were upregulated and 2849 m6A peaks downregulated. It was found that genes with the dysregulated m6A peaks were enriched in the pathways in cancer, Rap1 signaling pathway, and insulin resistance. Additionally, 612 genes with abnormal regulation of m6A peaks and RNA expression were identified by combining MeRIP-seq and RNA-seq data. Through KEGG analysis, the 612 genes were enriched in cancer-related signaling pathways, such as the cGMP-PKG signaling pathway, and the Rap1 signaling pathway. What’s more, GSEA enrichment analysis showed these genes were enriched in cell cycle phase transition, cell division, cellular response to DNA damage stimulus, and chromosome organization. To further explore the relationship between differential m6A modified genes and clinical parameters of LUAD patients, we searched The Cancer Genome Atlas (TCGA) and identified 2 genes (FCRL5 and GPRIN1) that were associated with prognosis and diagnosis of LUAD patients. Furthermore, we found a positive correlation between GPRIN1 and m6A reader YTHDF1 in GEPIA2 database. It was verified that YTHDF1 binds to GPRIN1 mRNA and regulate its expression. Our study results suggests that m6A modification plays important role in the progression and prognosis of LUAD and may be a potential new therapeutic target for LUAD patients in the future.